上古汉语虚词“于”和“以”的语法地位再探 = Further analysis of grammatical function of Yu and Yi in archaic Chinese - 李凯渊 Li, Kai Yuan (2013)
Both “YU” and “YI” are important functional words in Archaic Chinese. Many scholars agree that both “YU” and “YI” are preposition and have conducted in-depth research on both “YU” and “YI”. Recently, Aldridge (2012) proposed an analysis of the functional morpheme “YI” in Late Archaic Chinese as a high applicative (in the sense of Pylkkanen 2002) and also challenges the traditional assumption that “YI” is a preposition.There are two main facts that Aldridge has observed about the functional morpheme “YI” in Late Archaic Chinese: 1. The structural asymmetry between constructions involving preverbal “YI-DP” and those involving post-verbal “YI-DP” 2. The structural asymmetry between “YU” and “YI” construction. Evidence for Aldridge’s proposal comes primarily from structural asymmetries between “YI-DP VP” and “VP YI-DP” orders, which would not be accounted for if “YI-DP” were a PP. And the asymmetry between “YU” and the “YI” applicative construction provides further evidence that “YI” is not a preposition. This paper argues that the functional morpheme “YI” cannot be proposed as a high applicative simply based on structural asymmetry. This paper proposes an analysis that the asymmetry between “YU” and the “YI” applicative construction is related to the semantic role, which follows YU and YI. The difference between “YI” and “YU” can be observed on the Multi-Layer Semantic Map: “YU” precedes to both space domain and non-space domain while “YI” can only precede to non-space domain. On the other hand, this paper also mentioned that the surface position of YI-DP was controlled by the semantic roles follows YI that leads to the structural asymmetry between “YU” and “YI”.